Chagas disease and liver transplantation: Experience in Argentina using real‐time quantitative PCR for early detection and treatment. Issue 6 (10th November 2017) - Balderramo, Domingo; Bonisconti, Florencia; Alcaraz, Alvaro; Giordano, Enzo; Sánchez, Ariel; Barrabino, Martín; Caeiro, Juan Pablo; Alvarellos, Teresita; Maraschio, Martín
Abstract: Background: Chagas disease (CD) is an endemic zoonosis that occurs in Latin America and is caused by the parasite Trypanosoma cruzi . Early detection of T. cruzi in liver transplant recipients at risk may avoid complications from CD. The aim of this study was to examine the pre‐operative evaluation and follow‐up of CD after liver transplantation (LT) of patients at risk of CD using real‐time quantitative polymerase chain reaction (qPCR) for T. cruzi . Methods: Between January 2009 and June 2016, 13 (12.7%) of 102 LTs performed in recipients at risk for CD without specific postoperative prophylaxis were prospectively evaluated using qPCR for T. cruzi . Four seronegative patients received livers from seropositive donors (R−/D+) and 9 seropositive recipients received livers from seronegative donors (R+/D−). A cohort of 89 patients without risk for CD during the same time period was analyzed as controls. Results: A positive qPCR for T. cruzi prior to LT was found in 2/9 (22.2%) seropositive recipients, and both achieved early response after therapy. The cumulative incidence of positive parasitemia after LT was higher in R+/D− than R−/D+ (37.7% vs 0%, P  = .17). R+/D− transplant patients with positive qPCR achieved therapeutic response without manifestations of acute CD. LT outcomes at 1 year were similar in patients at risk of CD and in controls not at risk for CD. Conclusion: A small proportion of T. cruzi ‐seropositive candidates presented positive parasitemia before LT. After LT, qPCR allowed detection of parasitemia leading to use of preemptive therapy in all R+/D− with T. cruzi replication. No cases of T. cruzi parasitemia occurred in R−/D+.